Tar Spot of Maize in Florida: PP378, 9/2024 - Ferreira, Larissa C.; Moura, Vitor A. S.; Resende, Marcio F. R.; Xavier, Katia V. (EDIS, 2024)
Tar spot, a fungal foliar disease, affects most maize types commonly grown in Florida, such as sweet corn, field corn, and criollo corn. This disease is characterized by brown-to-black, raised structures called stromata, which are embedded in leaf tissue. As a polycyclic disease, tar spot lesions can increase in number as the disease progresses throughout the growing season, leading to reduction of photosynthetic area on the leaves. Tar spot has recently emerged as a significant threat in Florida and in the United States, with reports of up to 100% incidence in maize fields in south Florida. Tar spot occurrence and development in Florida is influenced by several factors, such as environmental conditions, maize types, crop maintenance, and corn growth stages. The purpose of this publication is to promote awareness among Florida growers regarding this newly identified disease and its management practices.